The human focus in KM/IC for innovation in smart/future universities: literature review - Ahmetoglu, Sehnaz; Alyami, Nuha; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
Knowledge management has been viewed as one of the most important developments in the fields of information studies and management in the modern times. By obtaining, organizing, documenting and sharing knowledge, Knowledge management helps complex organisations make better decisions and solve their problems efficiently and effectively. As highest centres of learning, universities should build information infrastructure and create an atmosphere where educational and non-educational staff, students, researchers, patrons and other stakeholders can take part in various knowledge management sharing actions. The role of knowledge workers in this regard is quite important. By promoting knowledge discovery and use, knowledge workers can bring about changes in the university’s organisational cultures and individual behaviours relative to knowledge. Universities can play an important role in the building and unrestricted development of a knowledge-based society by recruiting skilled and competent knowledge workers and empowering them to manage the knowledge assets effectively.